Puzzles from the Arctic – deciphering temporal distribution, ecological niche and life history of two Appendicularia species in Kongsfjorden, Svalbard Islands - Nicolai, Alessandro; Paladini de Mendoza, Francesco; Ingrosso, Gianmarco; Langone, Leonardo; Tesi, Tommaso; Titocci, Jessica; Giordano, Patrizia (Frontiers in Marine Science, 2025)
Understanding the ecology and population dynamics of Arctic appendicularians is increasingly important as oceanographic and climatic conditions continue to change in the high polar systems. Here, the adoption of sediment traps allowed for efficient fixation and preservation of their soft bodies, and validated a representative point sampling for these species regarding their patchy distribution. This study investigates the temporal distribution, phenological rhythms and oceanographic drivers affecting two appendicularian species, Oikopleura (Vexillaria) vanhoeffeni and Fritillaria borealis in Kongsfjorden (Svalbard), a high-Arctic fjord occasionally influenced by Atlantic Water (AW) intrusions and variable sea ice conditions. Based on a time-series of sediment trap samples from 2010 to 2023, O. vanhoeffeni was consistently present and increased in occurrences after 2016. F . borealis , was not detected until 2017, appeared episodically, likely as a non-resident species seasonally introduced into the fjord. Temporal succession of the two species appeared to be influenced by the combination of (i) seasonal variability of thermohaline conditions, (ii) glacial meltwater influencing water mass structure, and (iii) turbidity fluctuations from marine and continental inputs. Oikopleura vanhoeffeni exhibited a well-defined annual cycle with juveniles appearing in autumn (post-reproductive phase), growing through winter-spring, and maturing into reproductive adults by summer. Growth during the polar night was primarily influenced by hydrological conditions, whereas food availability became more important in summer. In contrast, F. borealis showed a peak of adults in spring-summer and juveniles in autumn-winter, indicating a reproductive phase following the spring phytoplankton bloom. These findings contribute to understanding the ecology and population dynamics of Arctic appendicularians under shifting oceanographic and climatic conditions, emphasizing their potential role as sentinel species in a rapidly changing polar environment.